ANALISIS GAYA KEPEMIMPINAN MANAJER PERAWAT TERHADAPKEPUASAN KERJA STAF PERAWAT, LITERATURE REVIEW - Safi’i, Akhmad (UI Scholars Hub, 2023)
Several studies show that different leadership styles will influence job satisfaction. The aim of this study is to analyze the leadership style of nurse managers and the job satisfaction of hospital nursing staff. This research uses a Literature Review design with the help of the PRISMA diagram. Search for scientific research articles using Proquest and Google Scholar. Search with the keywords “Leadership Style” AND “Hospital Nurse Manager” AND “Job Satisfaction”. After carrying out the identification, screening and eligibility process of the 22 articles, 12 articles were selected that met the inclusion criteria. The leadership style models applied include transformational, relational, transactional, democratic, participative and achievement-oriented leadership and laissez faire. Of the 12 articles, 7 articles (58%) discussed the transformational leadership style of nurse managers. This transformational style is the most widely practiced and influences the performance satisfaction of nursing staff. There is a relationship between the leadership style of nurse managers and the job satisfaction of nursing staff in hospitals. The dominant leadership style carried out by nurse managers in several countries is a transformational leadership style which has a positive impact on job satisfaction. Transformative leadership style promotes nurse job satisfaction which is followed by increased performance.